Pembagian Harta Bersama di Pengadilan Agama Sibolga Akibat Perceraian Karena Konversi Agama Suami - Fiola Ayu Meisaro (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This study examines the practice of marital property division at the Sibolga Religious Court due to divorce caused by the husband's religious conversion. The phenomenon of divorce due to religious differences, especially religious conversion from Islam, creates legal complexities, particularly in determining rights and obligations related to marital property. This study employs a qualitative approach with an empirical legal research type, located at the Sibolga Religious Court. Data was obtained through in-depth interviews with judges, court clerks, and parties involved in the cases, as well as document studies of court decisions. The results indicate that the Sibolga Religious Court has absolute authority in handling divorce cases due to the husband's religious conversion and the division of marital property within them. Despite the religious conversion, the principles of Islamic marital property law (syirkah) remain the primary basis, considering the contribution of each party. Challenges include the complexity of proving contributions, often emotional negotiations between parties, and judges' efforts to achieve substantive justice. The implications of the decisions not only involve legal aspects but also social and psychological ones for the families. This study recommends the need for broader legal socialization regarding rights and obligations in interfaith marriages and increased public understanding of marital property dispute resolution procedures.